Impact of military type footwear and load carrying workload on postural stability. Issue 1 (2nd January 2019) - Chander, Harish; Knight, Adam C.; Garner, John C.; Wade, Chip; Carruth, Daniel; Wilson, Samuel J.; Gdovin, Jacob R.; Williams, Caleb C.
Abstract: Postural stability has been shown to be impacted by footwear and task performed. This study analysed the impact of two military footwear, standard boot (STB) and minimalist boot (MTB) on postural stability, before (PRE) and after (POST) a load carriage task. Sixteen participants were tested for postural stability using sensory organisation and motor control tests on Neurocom Equitest™. Postural sway, equilibrium scores and postural latencies were analysed using a two-factor repeated measures ANOVA: boot type (STB-MTB) × time (PRE-POST) load carriage task. Significantly greater postural sway variables, lower balance scores and slower postural latencies were seen in STB and POST load carriage conditions ( p  < .05). The results suggest that MTB exhibited greater balance compared to STB in balance conditions that rely on somatosensory feedback and that balance is lowered after a load carriage task. Decrements in postural stability could be attributed to boot design characteristics and muscular exertion due to the load carriage task. Practitioner Summary: Maintaining optimal postural stability is crucial in military. Impact of military footwear types and load carriage task on postural stability are addressed. Findings provide footwear design and physical exertion implications on postural stability leading to potential interventions that reduce postural stability decrements; thereby, reducing potential falls and fall related injuries.